2016
DOI: 10.1136/postgradmedj-2015-133530
|View full text |Cite
|
Sign up to set email alerts
|

Adult food-induced anaphylaxis hospital presentations in New Zealand

Abstract: BackgroundFood allergy including anaphylaxis is an increasing clinical problem in many countries. Little information is available regarding prevalence, causative foods and time trends in the New Zealand adult population.ObjectiveThis cross-sectional study investigated the incidence of hospital presentation with food-induced anaphylaxis in New Zealand among adults and adolescents over a 10-year period.MethodsMinistry of Health hospital discharge data from 2002 to 2011 were analysed using food allergy and anaphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
15
1
1
Order By: Relevance
“…14 An analysis of 20 years of UK FIA trends (1992-2012) found paediatric admissions (0-14 years) rose by 137% (rate ratio 1.05; 95% confidence interval (CI) 1.05-1.06; P < 0.001). 25 This study showed an increased rate over the 10-year period from 3.3 per 100 000 people in 2002 to 5.8 per 100 000 people in 2011 with the greatest increase in attendances seen in Pacific peoples. 23 This geographical gradation has previously been reported in the USA and Australia and has raised the question of the role of vitamin D deficiency in food allergy.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…14 An analysis of 20 years of UK FIA trends (1992-2012) found paediatric admissions (0-14 years) rose by 137% (rate ratio 1.05; 95% confidence interval (CI) 1.05-1.06; P < 0.001). 25 This study showed an increased rate over the 10-year period from 3.3 per 100 000 people in 2002 to 5.8 per 100 000 people in 2011 with the greatest increase in attendances seen in Pacific peoples. 23 This geographical gradation has previously been reported in the USA and Australia and has raised the question of the role of vitamin D deficiency in food allergy.…”
mentioning
confidence: 61%
“…25 M aori (1.4 to 5.7 per 100 000 people), Asians (4.1 to 5.5 per 100 000 people) and people of NZ European and 'Other' ethnicities (3.5 to 5.2 per 100 000 people) had more modest increases over the 10-year period reviewed. 25 M aori (1.4 to 5.7 per 100 000 people), Asians (4.1 to 5.5 per 100 000 people) and people of NZ European and 'Other' ethnicities (3.5 to 5.2 per 100 000 people) had more modest increases over the 10-year period reviewed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations